What Is a Teacher ? - Simon, Henry W. (New York : Collier, 1938)
The introductory portion of this report defines teacher education centers and briefly describes their developmental continuum. A synthesis of documents concerning student teaching and teacher education centers is followed by a list of features differentiating conventional programs, student teaching centers, and teacher education centers. Evaluation of center activities is incomplete; however, an abstract of a research document indicating that centers do make a difference is presented. An 11-item bibliography is included. (MJM)
Microfiche.
Keywords: Educational Innovation; Field Experience Programs; Program Descriptions; Student Experience; Student Teaching; Teacher Education; Teacher Education Programs